Laparoscopic-guided sclerotherapy of an abdominal lymphatic malformation: A case report - Paul McClure; Kate McNevin; Giri Shivaram; Caitlin Smith (Elsevier, 2024)
Introduction: While most lymphatic malformations (LMs) are treated by percutaneous sclerotherapy, intra-abdominal LMs may be difficult to access percutaneously due to their anatomic location. Case presentation: An 11-year-old otherwise healthy boy presented with abdominal pain and cross-sectional imaging (including CT scan and MRI) identified an intra-abdominal LM located in the lesser sac, bordered by the stomach, spleen, and pancreas. An attempt to access the lesion percutaneously was made, however this was unsuccessful due to overlying viscera. Given the morbidity associated with an open surgical approach, the patient underwent laparoscopic-guided doxycycline sclerosant injection. After the LM was exposed laparoscopically, a pigtail catheter was placed into the lesion using the Seldinger technique. Doxycycline sclerosant was instilled three times over the course of three days and the pigtail catheter was removed after the third instillation. The LM completed resolved in addition to the abdominal pain the patient was experiencing. After more than one year of follow up, the LM has not recurred. Conclusion: Abdominal LMs may be safely treated with a laparoscopic-guided doxycycline sclerosant injection when surgical excision would be exceedingly morbid and there is no safe percutaneous entry site.